PERAN MODERASI PASSION ANTARA EFIKASI DIRI DAN INOVASI TERHADAP MINAT WIRAUSAHA - Wardoyo Putro, Prima Utama (LP2M Institut Teknologi dan Bisnis Asia Malang, 2021)
Recently, coffee is no longer a drink for parents. Many millennials are starting to enjoy drinking coffee. This can be seen from the growth of coffee shops in the Madiun City which continues to grow from time to time. This study aims to find empirical evidence of the reasons coffee shop owners are interested in entering the coffee business. This research is focused on aspects of self-efficacy, innovation, and passion. This research is a quantitative using a saturated sample technique, namely observing all populations. This research was conducted in Madiun City with sample size of 50 coffee shop entrepreneurs. The research instrument test used validity and reliability tests, while the data analysis technique used was MRA. The results are: self-efficacy has no significant effect on entrepreneurial interest, innovation has a significant positive effect on entrepreneurial interest, and passion does not mediate the relationship between self-efficacy and innovation on entrepreneurial interest.